MAHKAMAH KONSTITUSI DALAM MENEGAKKAN KEADILAN KONSTITUSIONAL DI ERA MODERN - Ilham, Muhammad (Legal Standing : Jurnal Ilmu Hukum, 2024)
This research aims to examine the role of the Constitutional Court (MK) in upholding constitutional justice in Indonesia in the modern era using a substantive justice approach. The research method used is normative juridical. The data used is secondary data, obtained from library materials through literature and documentation studies, then analyzed qualitatively. Descriptive data analysis techniques. The results showed that in the concept of "upholding justice" as an effort to achieve substantive justice, the Constitutional Court not only considers evidence and judges' beliefs, but also ensures that the decisions it makes have a positive impact on society. In practice, the Constitutional Court often makes ultra petita decisions, i.e. decisions that go beyond the demands of the disputing parties, to ensure optimal protection of every constitutional and human rights. This gives rise to the idea that the Constitutional Court plays a tactical role in making sure that laws and court rulings uphold procedural and constitutional rights while also promoting the growth of a just and democratic society. The study's key finding is that the Constitutional Court plays a crucial role in upholding social justice and the coherence of Indonesia's constitution in light of the changing needs and dynamics of modern society.